Quality Improvement of Indonesian University in The Face of Globalization - Lantara, Niniek Fariaty (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
This article shed light on sustainable quality improvement of Indonesian universities by embracing autonomous principle as the propulsion for a more dynamic and accountable system in order to back up a reliable autonomy with accreditation to assure the quality of graduate students, and self evaluation to guarantee an apt decision making based on empirical data and information. Therefore, it is vital to reassess university vision and mission of teaching, researching, and community service, especially in the face of a more democratic globalization era sustained with science and technological development. Government, universities, and other research institutions, together with industrial sector, are highly potential to form a synergistic triangle to jointly handle internalization transfer and strategic technological development to enhance productivity and national competitiveness sustainably. Autonomy is a right or authority provided by the authorized party or government, while academic freedom is a kind of freedom owned by academicians in performing their duty and their functional activity, namely education and scientific research. The development of University accountability is meant to make the best use of university resources for activities sustaining the stated goals.